The Slopeslides Potential Modeling Of Semarang City Roads - Wicaksono, Vinsensius Priyo; Pratikso; Karlinasari, Rinda (Aptek, 2023)
The purpose of this study was to determine influencing parameters and dominant causes of roads-slope failures, and to determine the potential risk of roads-slope failures modeling in the Semarang City Region. This quantitative descriptive research uses primary an secondary data collection methods, identification of factors that cause landslides, observation of field conditions and processing of spatial data. Slope stability data collection to obtain a database of road slopes and selection of road sections in "very prone to landslides" conditions from the Slope Hazard Map processed by spatial data, 3 out of 43 sections were selected, are Jl. Kyai Mojo I, Jl. Mr. Abdul Madjid Djojoadiningrat, and Jl. Gombel Lama. It is not a coincidence that they were at the same zone and types according from the Topographic Map, the Geological Map, and from the Soil Type Map. From the processed rainfall data for 10 years from 6 rain observation posts, it was found that these sections are in the moderate rainfall zone in the modeling of rainfall intensity for return periods of 2, 5, 10 and 25 years. Slope stability analysis uses 2D finite element modeling from soil sampling data in the field which is modified into unsaturated conditions with parameters according to the results of soil investigations and saturated conditions with an assumptions on rainfall loads on slopes and soil suction. The significant difference in the SF results between conditions proves that the rainfall affects the stability, even though the model cannot represent all slopes condition.